Foods may modify responsiveness to cancer immune checkpoint blockers by altering both the gut microbiota and activation of estrogen receptors in immune cells - Hilakivi-Clarke, Leena; Verma, Vivek; McDermott, Maddie; Koak, Pal; Andrade, Fabia de Oliveira (Frontiers in Microbiomes, 2022)
Estrogen receptor alpha positive (ERα+) breast cancers are refractory to immune checkpoint blocker (ICB) monotherapy, while ICBs are part of a standard of care for triple negative breast cancers (TNBCs). Besides tumor ERα expression, another difference between the two types of breast cancers is that only ERα+ patients exhibit elevated tumor estradiol (E2) levels, compared with surrounding normal tissue. Recent evidence suggests that inhibition of ERα or activation of ERβ or G protein-coupled estrogen receptor (GPER) in immune cells in the tumor microenvironment (TME) increases tumor CD8+ T cell infiltration and boosts cancer ICB response. Ovarian and adipose-produced estrogens activate all three ERs equally, but plant estrogens (phytochemicals) preferentially activate ERβ or GPER. The gut microbiota is a key player in determining response to ICBs, and high abundance of Firmicutes and high fecal levels of short chain fatty acids (SCFAs) that are mainly produced by Firmicutes, are linked to improved effectiveness of ICB therapy. Interestingly, the gut microbiota of ERα+ breast cancer patients contain significantly lower abundance of Firmicutes species than the gut microbiota of TNBC patients. Many factors modify the gut microbiota, especially diet. The gut microbiota altering diets include (i) foods high in ERβ and GPER activating plant phytochemicals or (ii) SCFAs producing fiber that also reduces circulating estrogen levels, (iii) estrogen levels reducing fasting/caloric restriction, or (iv) ketogenic diet which reduces fecal SCFA levels but increases hepatic production of SCFA receptor activating ketone bodies. It is thus possible that certain foods or dietary patterns can modify both the gut microbiota and activation of the estrogen receptors in the tumor immune cells, and consequently regulate the effectiveness of ICB therapy against cancers.